The impact of combined thymol and rosmarinic acid on the intestinal microbiota and barrier function of the piglets challenged by Escherichia coli K88 - Runlin Li; Xuedong Ding; Mingkang Lei; Panpan Li; Ilias Giannenas; Jing Wang; Weiyun Zhu (Animal Nutrition)
It has been found that thymol (Thy) and rosmarinic acid (Ros-A) improve the growth performance of piglets and relieve intestinal inflammation in animals. The effects of Thy and Ros-A separately or in combination (Thy × Ros-A) on the intestinal function and health of piglets challenged with Escherichia coli K88 (E. coli K88) were investigated. A total of 30 piglets aged 21 d were assigned to 5 groups (n = 6). The control (Con) and K88 groups piglets received a basal diet, while the Thy, Ros-A, and Thy × Ros-A groups were fed a basal diet supplemented with 500 mg/kg Thy, 500 mg/kg Ros-A, and 250 mg/kg Thy + 250 mg/kg Ros-A, respectively. On the 19th and 20th day, piglets in the K88, Thy, Ros-A, and Thy × Ros-A groups were orally administered 10 mL of phosphate-buffered saline (PBS) containing approximately 1 × 109 CFU/mL of E. coli K88, while the Con group received an equal volume of PBS. The results showed that the Thy × Ros-A treatment reduced the damage to ileal villi induced by the E. coli K88 challenge, leading to longer villi in the ileum (P < 0.05). Thy and Ros-A modulated the composition of the ileal microbiota. Compared to the K88 group, the Thy × Ros-A group had a higher abundance of Lactobacillus and Romboutsia, while Escherichia-Shigella and Desulforvibrio were lower (P < 0.05). Additionally, the Thy × Ros-A group showed elevated levels of gene and protein expressions for zonula occludens-1, occludin, and claudin-1 compared to the K88 group (P < 0.05). In conclusion, combining Thy and Ros-A reduced ileal damage and relieved the inflammation in weaned piglets challenged with E. coli K88 by regulating intestinal microflora and improving barrier function.